Thermal reliability of a bilayer of Ni(P)/Cu as a diffusion barrier for Cu/Sn/Cu bonding - Lee, Byunghoon (2021)
This study examines the effects of barrier layers on the aging behavior of Cu/Sn bonding for three-dimensional (3D) integration. We compare the behavior of different bonding structures [Cu/Sn with no barrier, Ni(P) barrier, and Ni(P)/Cu bilayer barrier] after aging samples at 150 °C for long durations (up to 900 h). While the samples with no barrier allowed extensive Cu diffusion and the formation of Kirkendall voids, the Ni(P) barrier samples broke down as Ni outdiffused into the Sn layer. The bilayer barrier samples demonstrated excellent aging stability with the thin Ni(P)/Cu bilayer effectively suppressing Ni outdiffusion.